Fraser, Nancy. Fortunes of Feminism. From State-Managed Capitalism to Neoliberal Crisis. (2015)
Fraser, Nancy. Fortunes of Feminism. From State-Managed Capitalism to Neoliberal Crisis. London / New York: Verso, 2013. 248 pp.